Hubungan Kegiatan Ekstrakurikuler Pramuka Dengan Kedisiplinan Belajar Siswa Kelas IV SDN Bangunrejo Kidul 4 - Maylita, Fransisca; Malaikosa, Yes Matheos Lasarus; Putra, Army Al Islami Ali (Global Education Journal, 2023)
Scouting extracurricular is one of the school programs in the form of interesting and directed activities carried out in the open air and has the aim of forming character, morals, and noble character. The purpose of this study was to find and collect data on the relationship between Scouting extracurricular and student discipline at SDN Bangunrejo Kidul 4, Kedunggalar District, Ngawi Regency. This study is an Expost Facto study. The population in this study were grade IV students of SDN Bangunrejo Kidul 4, Kedunggalar District, Ngawi Regency, then took a sample of all 85 people who participated in Scouting extracurricular activities using the Probability sampling technique. Data collection techniques used questionnaires and documentation. Data analysis used validity tests, reliability tests which were then tested for correlation using the SPSS application. The results of this study indicate that there is a strong relationship between Scouting extracurricular and learning discipline of grade IV students of SDN Bangunrejo Kidul 4, Kedunggalar District, Ngawi Regency. So, it can be concluded that the hypothesis that states there is a significant relationship between Scout extracurricular activities and student learning discipline at SD Negeri Bangunrejo Kidul 4 is accepted.